Recording what happens in the under-16 consultation. Issue 2 (1st April 2006) - McGough, Pauline; Thow, Chris; Butt, Ambreen; Lamont, Myra; Bigrigg, Alison
Abstract : Background: Clinical staff offering sexual health services to young people need to balance the rights of the young person to confidentiality and good quality advice with the need to protect their wider interests. The needs of young clients may be complex and raise ethical and medico-legal questions for the staff involved in their care. Methods: In our large, integrated sexual health service, a 'recording form' was introduced to prompt staff to record data systematically pertinent to consultations in clients under 16 years of age, to understand what kind of presentations dominate in these consultations, and to establish how common child protection concerns are. Results: From April to October 2004, more than 500 forms were completed in our service. The age range for female clients was 12–15 years, with the median age of first sexual intercourse 14 years. Most respondents were in consensual relationships with partners of around their own age, but 10% had been in relationships of less than a week's duration. Most had not told their parents of their sexual activity and did not intend to. Child protection issues did occur, although not commonly. Conclusions: Most clients initially present requesting emergency contraception or pregnancy testing, and the inference is that unprotected sexual intercourse is common in this group of clients before they seek our services. The data collected give a valuable overview of the type of issues dealt with in the clinical context and can help to target training and teaching, in addition to potentially highlighting child protection issues.